Realizing Islamic Education Based on Religious Moderation with the Wasathiyah Islamic Paradigm from the Perspective of the Qur'an - Yazida Ichsan; Sahiron Syamsudin; Zalik Nuryana; Sukiman (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – Today, Muslims face considerable challenges in the era of the industrial revolution. On the one hand, there is the threat of liberalization that erodes spiritual values and Islamic teachings fundamentally. On the other hand, there is radicalization that uses violence in the name of religion, such as threats, terror, disbelief, and murder. They are serious problems that require efforts to understand the linkage between intolerant behavior and religious teachings. Design/methods/approach – This study is library research conducted through the steps of recording, clarifying, reducing, and presenting data using documentation methods from primary and secondary sources. The data analyzed by the content analysis method includes the meaning of wasathiyah Islam, religious moderation, the concept of wasathiyah Islam in the Qur'an, Surat Al-Baqarah verse 143, and moderation-based Islamic education. Findings – This research found that religious moderation can be applied to Islamic Education subjects through various approaches. Subjects such as Aqidah, Akhlaq, Fiqh, Tarikh, and Al-Qur'an Hadith integrate the wasathiyah values by emphasizing tolerance, dialogue, justice, and benefit from an Islamic perspective. Learning approaches, like problem-solving, inquiry, and discussion, have encouraged students to think multiperspective, discover new knowledge, and respect the ideas of others, both inside and outside of school. Research implications/limitations – This research provides important implications for the development of Islamic education based on religious moderation, especially through a curriculum that can integrate the values of tolerance, justice, and balance in learning. However, it is still limited to a literature approach, so further research is required with an empirical approach to measure the effectiveness of applying these values in various educational contexts. Originality/value – This research offers a unique perspective by using the concept of wasathiyah Islam to support Islamic education based on religious moderation. The novelty value lies in the elaboration of the implementation of moderation in various subjects, such as Aqidah, Akhlaq, Fiqh, Tarikh, and Al-Qur'an Hadith, which can be a model for the development of inclusive and tolerant education.